2015
DOI: 10.1080/00958972.2015.1037299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral characterization, crystal structures of lanthanide(III) pyrrolidine dithiocarbamate complexes and their catalytic activity

Abstract: A series of lanthanide(III) pyrrolidine dithiocarbamate complexes [Ln(Pyrrol-Dtc) 3 (Phen)] {Pyrrol-Dtc = pyrrolidine dithiocarbamate; Phen = 1,10-phenanthroline; Ln = La(III), Ce(III), Pr(III), Nd(III), Sm(III), Gd(III), Tb(III), Dy(III), Er(III)} have been synthesized and structurally characterized. The molecular structures of [La(Pyrrol-Dtc) 3 (Phen)], [Pr(Pyrrol-Dtc) 3 (Phen)], [Sm (Pyrrol-Dtc) 3 (Phen)], and [Dy(Pyrrol-Dtc) 3 (Phen)] have been confirmed using single crystal XRD studies.The results reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(46 reference statements)
2
9
0
Order By: Relevance
“…The synthesis of complexes 4 (cycLn 1 -phLn 2 ) was achieved by coordinating lanthanide chloride with one equivalent of complex 3 and three equivalents of ammonium pyrrolidine-1-carbodithioate at room temperature, followed by precipitation with diethyl ether from methanol. The proton nuclear magnetic resonance ( 1 H NMR) spectra of the La motif structure showed that three pyrrolidine dithiocarbamates were coordinated to the complex, which is consistent with a previous report 32 . This synthetic strategy provides a platform to obtain hetero-dinuclear complexes that consist of chemically similar lanthanide ions, one of which is not present in both ligand structures.…”
Section: Resultssupporting
confidence: 91%
“…The synthesis of complexes 4 (cycLn 1 -phLn 2 ) was achieved by coordinating lanthanide chloride with one equivalent of complex 3 and three equivalents of ammonium pyrrolidine-1-carbodithioate at room temperature, followed by precipitation with diethyl ether from methanol. The proton nuclear magnetic resonance ( 1 H NMR) spectra of the La motif structure showed that three pyrrolidine dithiocarbamates were coordinated to the complex, which is consistent with a previous report 32 . This synthetic strategy provides a platform to obtain hetero-dinuclear complexes that consist of chemically similar lanthanide ions, one of which is not present in both ligand structures.…”
Section: Resultssupporting
confidence: 91%
“…So, the geometry optimization of the Sm 3+ complex was performed with initial coordinates taken from the crystallographic data of Sm(pdtc) 3 (phen). 24 From the other side, the experimental structural data were used as a benchmark for estimation of the calculated parameters. The Eu(pdtc) 3 (phen) complex was modeled based on our X-ray diffraction data, which predicted isostructural Sm 3+ and Eu 3+ complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The crystal structure of the Sm(pdtc) 3 (phen) complex was reported previously with single crystals obtained by storing the dissolved complex in chloroform in an airtight bottle with diethyl ether. 24 In our work, single crystals of Sm(pdtc) 3 (phen) were prepared by recrystallization of the complex in acetonitrile solution. About 10 mg of the complex was partially dissolved in acetonitrile, leaving a small amount undissolved at the bottom acting as seeds.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methylene (CH2) protons of pyrdtcligands gave two pseudo triplets around  3.8 and 1.3. In addition, in the spectrum of 3b three sharp resonances due to free ethanol are observed[23]. These spectral features of 3b and 3b' suggest that the EtOH (or MeOH) molecule in the 9:9-coordinate complex dissociates in a chloroform solution to exist as an 8:8-coordinate dinuclear bphz-bridged complex.3.4.2 UV-visible absorption and MCD spectraUV-visible absorption and MCD spectra of the pyrdtccomplexes, 1b-5b, were measured in CH2Cl2 solutions.…”
mentioning
confidence: 97%